Fitness boxing the ultimate workout / Andy Dumas and Jamie Dumas - Dumas, Andy; Dumas, Jamie (The Crowood Press Ltd, 2014)
"The benefits of boxing training are many: weight loss and toning, improved speed, strength, stamina, coordination, balance, and flexibility. This book covers all the techniques used in a boxer's training program, and shows how to tailor these to suit individual needs through the use of color photographs and step-by-step guidance. It's a comprehensive guide to a non-contact cardiovascular workout that's safe, effective, and enjoyable. This title has been endorsed by the World Boxing Council." -- Publisher's annotation